PHENOLIC ACIDS AND FLAVONOIDS IN HYPERICUM PERFORATUM L. HAIRY ROOTS - OLIVER TUSEVSKI; SONJA GADZOVSKA SIMIC (International Journal of Pharma and Bio Sciences, 2013)
Investigations have been made to develop an efficient protocol for identification and quantification of phenolic acids and flavonoids in hairy roots (HR) of Hypericum perforatum L. HR were induced from root segments of in vitro grown seedlings from H. perforatum, after co-cultivation with Agrobacterium rhizogenes A4. Transgenic status of HR was confirmed by PCR analysis using rolB specific primers. HR grew rapidly on hormone-free medium and had plagiotropic growth with vigorous production of lateral roots. Phenolic acids and flavonoids in control roots and HR were analyzed using HPLC/DAD/ESI-MSn. Quinic acid was the only detectable phenolic acid in HR. Transgenic roots produced flavonol glycosides such as quercetin 6-C-glucoside, rutin and isorhamnetin O-hexoside. Chromatographic analysis of flavonoid aglycones in HR resulted in the identiï¬cation of kaempferol. Transformed roots yielded higher levels of catechin and epicatechin than untransformed roots. H. perforatum HR represent promising experimental system for enhanced production of phenolic compounds.